Bacterial cellulose as carrier for immobilization of laccase: Optimization and characterization - Frazao, Claudio J. R.
Bacterial cellulose (BC) has attracted attention as a new functional material due to its excellent mechanical strength, tridimensional nanostructure, high purity, and increased water absorption, compared to plant cellulose. In this work, commercial laccase was immobilized on BC and the influence of enzyme concentration, contact time, and pH was optimized toward the recovery activity of immobilized laccase. This optimization was carried out using a 3(3) experimental design and response surface methodology. Enzyme concentration played a critical role in laccase immobilization. Under optimized conditions (0.15 L L-1 of enzyme concentration, 4.8 h of contact time, pH 5.4), the predicted and experimental response were equal to 47.88 and 49.30%, respectively. The thermal stability of the immobilized laccase was found to increase notably at 60 and 70 degrees C presenting stabilization factor equal to 1.79 and 2.11, respectively. The immobilized laccase showed high operational stability, since it retained 86% of its initial activity after seven consecutive biocatalytic cycles of reaction with 2,2-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid). Kinetic studies showed that the values of Michaelis-Menten constant and maximum reaction rate decreased upon immobilization (9.9- and 1.6-fold, respectively). Globally, the use of immobilized laccase on BC offers an interesting tool for industrial biocatalytic applications.